A questão do género no sector informal em Cabo Verde: um estudo sobre as rabidantes" do mercado "sucupira" na Ilha De Santiago - Grassi, Marzia (Africana Studia, 2020)
The paper is a report of my fieldwor k in Cape Vert in 1999 and 2000 concerning my PhD in Development economics. lt concerns the female entrepreneurs in the informal economic commerce sector and its gender implications. The goal is to show an important female economic strategy in the economic market of a developing country. The institutional economics focuses on the evolution of social institutions, such as the firm, which form the context in which individual decisions are made. Using the informal firm as a category of analysis and gender like a social construction we can decipher the form and the intensity of gender conflict in the informal mar ket in Cape Vert.